COMPARATIVE DESCRIPTION OF SILLERs FOR PERMANENT OBTURATION OF ROOT CHANNELS - Popovich, I.Yu.; Gasyuk, N.V.; Yeroshenko, G.A. (World of Medicine and Biology, 2010)
For permanent obturation of the root ductings on the final stage of treatment of the complicated caries stomatologists utillize sillers of different chemical groups. A question of sillers’ choice for today is enough debatable. It is necessary to notice as a result of comparison of sillers of different chemical groups, that concordantly the higher resulted criteria maximally close to these indexes is sillers on the basis of epon. This group of sillers is comfortable for bringing, has homogeneous consistency and provide maximal аdhesion to the surface of dentine of root-channel, here reducing the risk of origin of the second infecting of root-channel.